Rebound of Antibiotic Use and Respiratory Infections After Resumption of Normalcy From COVID-19 in Hong Kong - Ma ESK; Hsu E; Chow V; Chow T; Kung K; Au A; Chen H (Infection and Drug Resistance)
Edmond Siu-Keung Ma,1 Enoch Hsu,1 Vincent Chow,1 Tracy Chow,1 KH Kung,2 Albert Au,2 Hong Chen1 1Infection Control Branch, Centre for Health Protection, Department of Health, Hong Kong, Special Administrative Region, People’s Republic of China; 2Communicable Disease Branch, Centre for Health Protection, Department of Health, Hong Kong, Special Administrative Region, People’s Republic of ChinaCorrespondence: Edmond Siu-Keung Ma, Infection Control Branch, Centre for Health Protection, Department of Health, Kowloon, Hong Kong, Special Administrative Region, People’s Republic of China, Email edmond_sk_ma@dh.gov.hkPurpose: During COVID-19 pandemic, use of antimicrobial has been shown to be reduced coupled with various respiratory infections. We investigated whether this effect on reduction of antibiotic prescription can be sustained after resumption of normalcy and lifting of public health measures.Methods: We compared the wholesale supply of antimicrobials using mean annual Daily Defined Dose/1000 inhabitants (DID) in different sectors in pre-COVID-19 (2014– 2019), COVID-19 (2020– 2022) and post-COVID-19 (2023) periods. We grouped the data according to AWaRe categorisation namely Access, Watch and Reserve defined by WHO, and analysed the trends of the top 10 antibiotics and broad-spectrum antimicrobials. The trends in statutory notifiable diseases including scarlet fever, pneumococcal infections, chickenpox, tuberculosis, and pertussis and influenza-like-illness detected by sentinel surveillance system was analysed by negative-binominal regression.Results: Compared to baseline level, an overall reduction of 27.2% of antimicrobial utilization was observed during the pandemic years, with a rebound recorded in 2023, up to 89.5% of the pre-pandemic level. The access group of antimicrobials accounted for 57.9% in 2014 gradually increased to 60.2% in 2023 across the pandemic years. Concurrently, reduction in incidence of scarlet fever, pneumococcal infections, chickenpox, tuberculosis, pertussis and influenza-like-illness was observed during COVID-19 pandemic with statistical decreasing trend, p< 0.05 for scarlet fever, pneumococcal infections and chickenpox. Rebound in all these infections was reported in 2023, except for chickenpox which showed continued decrease in incidence.Conclusion: We demonstrated a substantial reduction of antibiotic use during the COVID-19 pandemic, which rebounded in 2023, likely due to increased incidence of respiratory diseases after lifting of public health and social measures. We urged for close monitoring of the antimicrobial resistance pattern of different bacteria due to the inter-connectiveness and global impact of these two pandemics.Keywords: antimicrobial resistance, antimicrobial utilization, antibiotics, COVID-19, surveillance